2014
DOI: 10.1242/bio.20148532
|View full text |Cite
|
Sign up to set email alerts
|

Rab11a is required for apical protein localisation in the intestine

Abstract: The small GTPase Rab11 plays an important role in the recycling of proteins to the plasma membrane as well as in polarised transport in epithelial cells and neurons. We generated conditional knockout mice deficient in Rab11a. Rab11a-deficient mice are embryonic lethal, and brain-specific Rab11a knockout mice show no overt abnormalities in brain architecture. In contrast, intestine-specific Rab11a knockout mice begin dying approximately 1 week after birth. Apical proteins in the intestines of knockout mice accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 40 publications
4
95
2
Order By: Relevance
“…Many of the aspects of the effects of Rab11a loss in this mouse were similar to those that we have observed including short microvilli and expansion of the intracellular lysosome system. However, in contrast with our studies, Sobajima, et al did not report the lateral microvilli that we observed in both mouse and cell line studies with loss of Rab11a (Sobajima et al, 2015). Nevertheless, they did notice mislocalization of the apical brush border protein DPPIV to the basolateral membranes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Many of the aspects of the effects of Rab11a loss in this mouse were similar to those that we have observed including short microvilli and expansion of the intracellular lysosome system. However, in contrast with our studies, Sobajima, et al did not report the lateral microvilli that we observed in both mouse and cell line studies with loss of Rab11a (Sobajima et al, 2015). Nevertheless, they did notice mislocalization of the apical brush border protein DPPIV to the basolateral membranes.…”
Section: Discussioncontrasting
confidence: 99%
“…In Rab11a DIEC duodenum samples and CaCo2-BBE Rab11a-KD cells, apically trafficked proteins were mislocalized, microvilli length was reduced and microvilli were aberrantly present on the basolateral membrane. While this work was in revision, another group also published information on a similar intestine-targeted Rab11a-knockout mouse model (Sobajima et al, 2015). Many of the aspects of the effects of Rab11a loss in this mouse were similar to those that we have observed including short microvilli and expansion of the intracellular lysosome system.…”
Section: Discussionsupporting
confidence: 61%
“…S3A). Previous work has shown that during brush border formation, the apical actin cytoskeleton is strongly regulated by signaling and/or trafficking processes that are dependent on the apical accumulation of Rab11A-positive recycling endosomes (Dhekne et al, 2014;Knowles et al, 2015;Overeem et al, 2015;Sobajima et al, 2015). We analyzed the distribution of Rab11A endosomes by using cells that had been stably transfected with a construct for doxycycline-inducible expression of dTomato-Rab11A.…”
Section: Acf7 Binds To Camsap3 and Participates In Its Apical Recruitmentioning
confidence: 99%
“…ACF7, CAMSAP2 and CAMSAP3 were not essential for the distribution of early cell polarity markers in twodimensional (2D) cultures; however, loss of ACF7 but not of the two CAMSAP proteins affected the formation of epithelial cysts in 3D cultures, indicating that ACF7 plays a more profound role in epithelial polarity than the CAMSAP proteins. Loss of CAMSAP3 led to more centrosome-centered microtubule organization, and this affected the organization of the actin cytoskeleton at the apical side of the cell, probably owing to mislocalization of recycling endosomes that are positive for Rab11A, which are an important component in apical polarity and brush border formation in intestinal cells (Bryant et al, 2010;Dhekne et al, 2014;Knowles et al, 2015;Overeem et al, 2015;Sobajima et al, 2015). Taken together, our study identifies ACF7 as an important regulator of apico-basal polarity in mammalian intestinal cells and demonstrates the importance of non-centrosomal microtubule organization for efficient epithelial cell polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Ras-related protein in brain 11a (Rab11a) is an important GTPase associated with recycling endosomes critical for both endocytic and exocytic protein pathways (57). It is mainly associated with the apical recycling endosome in polarized epithelia (21), and regulates the movement of known brushborder biomarkers dipeptidyl peptidase and alkaline phosphatase to the apical membrane (46). The roles of Rab11a in regulating traffic of sugar transporters to the apical membrane and in trafficking of a transporter to the apical membrane on the regulation of enzymes mediating the catabolism of its substrate have not yet been investigated.…”
mentioning
confidence: 99%